A Photoacoustic Probe for the Imaging of Tumor Apoptosis by Caspase‐Mediated Macrocyclization and Self‐Assembly. (20th February 2019) - Wang, Yuqi; Hu, Xiaoming; Weng, Jianhui; Li, Jinbo; Fan, Quli; Zhang, Yan; Ye, Deju
Abstract: Photoacoustic (PA) imaging shows promise in the sensitive detection of caspase‐3 activated in early tumor apoptosis in response to chemotherapy; smart PA probes are thus in high demand. Herein, we report the first smart PA probe (1‐RGD ) responsive to caspase‐3, enabling real‐time and high‐resolution imaging of tumor apoptosis.1‐RGD is designed to leverage the synergetic effect of active delivery and caspase‐3 activation. It is selectively recognized by active caspase‐3 to trigger peptide substrate cleavage and biocompatible macrocyclization‐mediated self‐assembly, leading to an amplified PA imaging signal and prolonged retention in apoptotic tumor cells. Strong, high‐resolution PA images are obtained in chemotherapy‐induced apoptotic tumors in living mice after intravenous administration with1‐RGD, facilitating sensitive reporting of caspase‐3 activity and distribution within tumor tissues.